2015
DOI: 10.1589/jpts.27.2303
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ankle strengthening exercises combined with motor imagery training on the timed up and go test score and weight bearing ratio in stroke patients

Abstract: [Purpose] The purpose of the present study was to compare the effects of ankle strengthening exercises combined with motor imagery training and those of ankle strengthening exercises alone in stroke patients. [Subjects and Methods] Thirty stroke patients were randomly assigned to one of the following two groups: experimental group (15 patients) and control group (15 patients). The experimental group underwent motor imagery training for 15 minutes and ankle joint strengthening exercises for 15 minutes, while th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 22 publications
(21 reference statements)
0
3
0
Order By: Relevance
“… 4 showed that MIP might contribute to both promote learning of postural tasks and improve dynamic balance in unstable and non-predictable environments. MIP has further been found to activate the neural regions involved in gait planing 8 , and might therefore contribute to enhance postural control in easily fatigable and physically impaired populations such as elderly persons 9 , 10 and stroke patients 11 14 . Specifically, decreased anteroposterior and mediolateral sway, as well as increased holding balance durations on one leg, were measured after MIP during static postural tasks (maintaining a stable stance).…”
Section: Introductionmentioning
confidence: 99%
“… 4 showed that MIP might contribute to both promote learning of postural tasks and improve dynamic balance in unstable and non-predictable environments. MIP has further been found to activate the neural regions involved in gait planing 8 , and might therefore contribute to enhance postural control in easily fatigable and physically impaired populations such as elderly persons 9 , 10 and stroke patients 11 14 . Specifically, decreased anteroposterior and mediolateral sway, as well as increased holding balance durations on one leg, were measured after MIP during static postural tasks (maintaining a stable stance).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in the condition of standing still, the distribution of foot pressure shows significant forward and outward tendencies. To compensate for this, the ankle strategy is used to maintain balance so that the ground reaction force mainly acts on the foot that is not paralyzed [4]. Consequently, this imbalance has a negative impact on gait ability, and addressing this problem is a very important goal in rehabilitation [5].…”
Section: Introductionmentioning
confidence: 99%
“…The ankle bears more weight per unit area than any other joint in the body 1 ) . The ankle joint is important for the balance strategy of the body 2 ) . Balance is a person’s ability to keep their center of gravity within the base of support or by restoring their center of gravity to that position under the force of gravity.…”
Section: Introductionmentioning
confidence: 99%